Synthesis and initial biological evaluation of substituted 1-phenylamino-2-thio-4,5-dimethyl-1H-imidazole derivatives - Yurttaş, Leyla; Duran, Murat; Demirayak, Şeref; Gençer Karaca, Hülya; Tunalı, Yağmur (My University, 2013)
In this work, some new 2-[(4,5-dimethyl-1-(arylamino)-1H-imidazol-2-yl) thio]-1-(aryl)ethanone derivatives were synthesized and investigated for their antibacterial, antifungal and anticancer activities. Toxicity of the most effective compounds was established by performing Brine-Shrimp lethality assay. Antifungal activity of the compounds was found to be higher than antibacterial and anticancer activities of the compounds.
Keywords: Anticancer; Antimicrobial; Brine-Shrimp Test; Imidazole